Half-Metallic Ferromagnetism in Chalcopyrite (AlGaMn)P2 Alloys - Byung-Sub Kang; Kwang-Pyo Chae; Haeng-Ki Lee (Advances in Condensed Matter Physics)
We studied the electronic and magnetic properties of (Al1−yMny)GaP2 (Ga-rich) and Al(Ga1−yMny)P2 (Al-rich) with y = 0.03125, 0.0625, 0.09375, and 0.125 by using the first-principles calculations. The ferromagnetic Mn-doped AlGaP2 chalcopyrite is the most energetically favorable one. The spin polarized Al(GaMn)P2 state (Al-rich system) is more stable than spin polarized (AlMn)GaP2 state (Ga-rich) with the magnetic moment of 3.8 μB/Mn. The Mn-doped AlGaP2 yields strong half-metallic ground states. The states of host Al, Ga, or P atoms at the Fermi level are mainly a P-3p character, which mediates a strong interaction between the Mn-3d and P-3p states.